Pengaruh Penggunaan Berbagai Media Tanam Pada Proses Pembibitan Durian (Durio zibethinus Murr. ) - Dini Ayesta Rency; Kiki Amelia; Wilna Sari; Mentari Larashinda (JURNAL AGROPLASMA, 2026)
This study aimed to evaluate the effect of different growing media on the early growth of durian seedlings (Durio zibethinus Murr.) and to determine the most effective medium for nursery production. The experiment was conducted using a Completely Randomized Design (CRD) with four treatments: P0 (topsoil + cow manure), P1 (topsoil + cow manure + rice husk), P2 (topsoil + cow manure + cocopeat), and P3 (topsoil + cow manure + sawdust) at a ratio of 1:1:1. Observed parameters included plant height, number of leaves, stem diameter, leaf width, leaf length, leaf color, and growing media pH. Data were analyzed using analysis of variance (ANOVA) followed by DMRT at a 5% significance level. The results showed that growing media significantly affected leaf length, while plant height, number of leaves, stem diameter, leaf width, leaf color, and media pH were not significantly different among treatments. Treatment P2 produced the longest leaves (13.26 cm) and showed the best overall growth performance. The addition of cocopeat improved moisture retention, aeration, and nutrient absorption efficiency, supporting vegetative growth. Therefore, P2 medium is recommended as the most effective growing medium for durian seedling production. Keywords: durian, growing medium, seedling, vegetative